A Comment on "Detecting Mother-Father Differences in Spending on Children: A New Approach Using Willingness-to-Pay Elicitation" - Nienke Buters; Jakub Prochazka; Katrin Schefbänker; Andreas Strobl; Karin Teichmann (Institute for Replication (I4R), 2024)
This report inspects the reproducibility of a study by Dizon-Ross and Jayachandran (2023), which focused on differences in parents' spending on their daughters relative to sons on a large sample of 6,673 observations in 1,084 households in Uganda. The original study found that the willingness to pay (WTP) of fathers for different goods for their daughters was lower than for their sons. We were able to computationally reproduce all original results using the original data and code. To test for recreate reproducibility, we tried to reproduce the results of the main analyses using a new code and different software. We were not able to complete the reproduction without analyzing the original code and processed dataset. It was not clear from the manuscript nor the online appendix how the authors dealt with the multilevel structure of the data and how they controlled for different goods, which served as stimulus material. Because the raw data did not have clear labels and the replication package did not include a codebook, we were also unable to identify the variables needed for each analysis. However, after analyzing the original code, we were able to reproduce the original results in MPLUS. The missing code book and missing transcription of survey questions caused complications for investigating robustness reproducibility. Although the authors collected a large number of variables and provided them in the dataset, it was not possible to identify their meaning. Therefore, we were not able to conduct further analyses regarding the main findings of the study. Consequently, we only focused on multicollinearity checks and different constellations of the control variables reported in the paper within the robustness checks. Our analyses showed that the results of the study are robust in this respect. In addition, the missing code book and transcription of survey questions did not allow for direct replicability of the study. Conceptual replicability was not investigated.
Keywords: 330